Gemcitabine and docetaxel versus doxorubicin as first-line treatment in previously untreated advanced unresectable or metastatic soft-tissue sarcomas (GeDDiS): a randomised controlled phase 3 trial. Issue 10 (October 2017) - Seddon, Beatrice; Strauss, Sandra J; Whelan, Jeremy; Leahy, Michael; Woll, Penella J; Cowie, Fiona; Rothermundt, Christian; Wood, Zoe; Benson, Charlotte; Ali, Nasim; Marples, Maria; Veal, Gareth J; et al.
Summary: Background: For many years, first-line treatment for locally advanced or metastatic soft-tissue sarcoma has been doxorubicin. This study compared gemcitabine and docetaxel versus doxorubicin as first-line treatment for advanced or metastatic soft-tissue sarcoma. Methods: The GeDDiS trial was a randomised controlled phase 3 trial done in 24 UK hospitals and one Swiss Group for Clinical Cancer Research (SAKK) hospital. Eligible patients had histologically confirmed locally advanced or metastatic soft-tissue sarcoma of Trojani grade 2 or 3, disease progression before enrolment, and no previous chemotherapy for sarcoma or previous doxorubicin for any cancer. Patients were randomly assigned 1:1 to receive six cycles of intravenous doxorubicin 75 mg/m 2 on day 1 every 3 weeks, or intravenous gemcitabine 675 mg/m 2 on days 1 and 8 and intravenous docetaxel 75 mg/m 2 on day 8 every 3 weeks. Treatment was assigned using a minimisation algorithm incorporating a random element. Randomisation was stratified by age (≤18 years vs >18 years) and histological subtype. The primary endpoint was the proportion of patients alive and progression free at 24 weeks in the intention-to-treat population. Adherence to treatment and toxicity were analysed in the safety population, consisting of all patients who received at least one dose of their randomised treatment. The trial was registered with the European Clinical Trials (EudraCT) database (no 2009–014907–29) and with the International Standard Randomised Controlled Trial registry (ISRCTN07742377), and is now closed to patient entry. Findings: Between Dec 3, 2010, and Jan 20, 2014, 257 patients were enrolled and randomly assigned to the two treatment groups (129 to doxorubicin and 128 to gemcitabine and docetaxel). Median follow-up was 22 months (IQR 15·7–29·3). The proportion of patients alive and progression free at 24 weeks did not differ between those who received doxorubicin versus those who received gemcitabine and docetaxel (46·3% [95% CI 37·5–54·6] vs 46·4% [37·5–54·8]); median progression-free survival (23·3 weeks [95% CI 19·6–30·4] vs 23·7 weeks [18·1–20·0]; hazard ratio [HR] for progression-free survival 1·28, 95% CI 0·99–1·65, p=0·06). The most common grade 3 and 4 adverse events were neutropenia (32 [25%] of 128 patients who received doxorubicin and 25 [20%] of 126 patients who received gemcitabine and docetaxel), febrile neutropenia (26 [20%] and 15 [12%]), fatigue (eight [6%] and 17 [14%]), oral mucositis (18 [14%] and two [2%]), and pain (ten [8%] and 13 [10%]). The three most common serious adverse events, representing 111 (39%) of all 285 serious adverse events recorded, were febrile neutropenia (27 [17%] of 155 serious adverse events in patients who received doxorubicin and 15 [12%] of 130 serious adverse events in patients who received gemcitabine and docetaxel, fever (18 [12%] and 19 [15%]), and neutropenia (22 [14%] and ten [8%]). 154 (60%) of 257 patients died in the intention-to-treat population: 74 (57%) of 129 patients in the doxorubicin group and 80 (63%) of 128 in the gemcitabine and docetaxel group. No deaths were related to the treatment, but two deaths were due to a combination of disease progression and treatment. Interpretation: Doxorubicin should remain the standard first-line treatment for most patients with advanced soft-tissue sarcoma. These results provide evidence for clinicians to consider with their patients when selecting first-line treatment for locally advanced or metastatic soft-tissue sarcoma. Funding: Cancer Research UK, Sarcoma UK, and Clinical Trial Unit Kantonsspital St Gallen.